-13=8x-2(x+5)

Simple and best practice solution for -13=8x-2(x+5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -13=8x-2(x+5) equation:


Simplifying
-13 = 8x + -2(x + 5)

Reorder the terms:
-13 = 8x + -2(5 + x)
-13 = 8x + (5 * -2 + x * -2)
-13 = 8x + (-10 + -2x)

Reorder the terms:
-13 = -10 + 8x + -2x

Combine like terms: 8x + -2x = 6x
-13 = -10 + 6x

Solving
-13 = -10 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-13 + -6x = -10 + 6x + -6x

Combine like terms: 6x + -6x = 0
-13 + -6x = -10 + 0
-13 + -6x = -10

Add '13' to each side of the equation.
-13 + 13 + -6x = -10 + 13

Combine like terms: -13 + 13 = 0
0 + -6x = -10 + 13
-6x = -10 + 13

Combine like terms: -10 + 13 = 3
-6x = 3

Divide each side by '-6'.
x = -0.5

Simplifying
x = -0.5

See similar equations:

| 7x+17+3x+20=90 | | 4-3x=-10-5x | | -5+4x+x+10=-35 | | 2x+4=2x-3 | | 2-3(3q+6)=8 | | 120x^5+28x^4-60x^3= | | 4x-9=-20 | | x-.6x-.17=.33(x-.8) | | 3y+17=43 | | 25x+10y=6.50 | | -2(x+3)=-28 | | 7x+6x-66=88-9 | | [3-x]=13 | | 8x-6=6x-44 | | 6m=4(-2)-2 | | 3y+3(y-2)=10y-2(y-4) | | 6=9x-18 | | -2g+(-16)=4 | | 11y-4=19y+52 | | .07x-.02=.05-.03(4x+2) | | 7x+1.50=29.50 | | -15.75+(-12.76)=n | | -x-1-x-8=3 | | 2xy+5x+6xy+3xy= | | 8x+7+9x+6=30 | | -27x=9 | | -7x+10+8x=7+x+3 | | -7+4x-3x=-19 | | 9(9x-3)= | | 0.05x+0.10(x+6)=2.40 | | -7+4x-3x=-29 | | -3x+10x-9=-30 |

Equations solver categories